Estratégias de dominação empresarial e resistências comunitárias na Amazônia maranhense - CASTRO, Raifran Abidimar de (Universidade Federal do Pará, 2018)
This research had as object of study the relationship between the companies Vale S/A and Suzano Papel Celulose S/A, with their rural communities of the settlement Francisco Romão, in Açailândia (MA), and the Extractive Reserve of the Ciriáco, Cidelândia (MA). This study aimed to analyze/interpret the repercussions of these relations in everyday life in the community, and in forms of corporate performance before the settlers and the tappers coconut. To access all the intricacies of these relations adopted the theory of Pierre Bourdieu as a theoretical-methodological axis; interviews were held with representatives of the communities and enterprises; complementing with documentary analysis and in the field. It was identified that companies seek, with its strategies of domination, using mainly their financial and cultural capitals, extend its powers on communities. Vale and Suzano exploit the economic weaknesses of the settlers and the tappers coconut, to establish a representation that strengthens its corporate powers. In relation to the settlers and the tappers coconut, it is noteworthy that it must strengthen them to the political struggles, legal, and mainly symbolic, considering that it was identified important demonstrations of resistance to business strategies. It was found that, while there is commitment of the valley and the Suzano in implementing strategies of domination, the communities have lit in their practices the essences of everyday resistance in defense of their rights.